Captain Jack and the pirates - Bently, Peter, 1960- (Dial Books for Young Readers, an imprint of Penguin Group (USA), 2016)
When brave mariners Jack, Zack and Caspar build a galleon then set off on an imaginary adventure at sea, they face pirates, a storm, and a shipwreck.